2021
DOI: 10.1093/g3journal/jkab002
|View full text |Cite
|
Sign up to set email alerts
|

De novowhole-genome assembly and resequencing resources for the roan (Hippotragus equinus), an iconic African antelope

Abstract: Roan antelope (Hippotragus equinus) is the second largest member of the Hippotraginae (Bovidae), and is widely distributed across sub-Saharan mesic woodlands. Although listed as Least Concern across its African range, population numbers are decreasing with many regional Red List statuses varying between Endangered and Locally Extinct. Although roan antelope has become an economically-important game species in Southern Africa, the vast majority of wild populations are found only in fragmented protected areas, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…In both analyses, the scimitar-horned oryx ( Oryx dammah , SB20612, Humble et al 2020) was used as the outgroup (not shown). Roan and sable antelope raw data are from Gonçalves et al (2021) and Koepfli et al (2019). Photo credits: see fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In both analyses, the scimitar-horned oryx ( Oryx dammah , SB20612, Humble et al 2020) was used as the outgroup (not shown). Roan and sable antelope raw data are from Gonçalves et al (2021) and Koepfli et al (2019). Photo credits: see fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used published raw sequencing read data of three roan ( Hippotragus equinus ) (Gonçalves et al 2021), eight sable antelopes ( Hippotragus niger ) (Koepfli et al 2019) from contemporary samples, and the scimitar-horned oryx ( Oryx dammah ) (Humble et al 2020) (supplementary table S4) in our analyses. The reads for these samples were treated in the same way as described above with the exception that merged and unmerged reads were both mapped, that the maximum overlap parameter in FLASH v1.2.11 was adjusted according to sequencing cycle length and that no rescaling was performed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations